if f(u)=16^u,so
f(a)=16^a , f(b)=16^b
f(a) x f(b)=16^a x 16^b=16^(a+b)=f(a+b)
2007-03-18 23:00:36
·
answer #1
·
answered by shiva 3
·
0⤊
0⤋
I don't think you can show that, if the f of u is 16 to the u, then the f of a times the f of b should be 16 times 16 to the a times b.
2007-03-18 22:52:06
·
answer #2
·
answered by peteryoung144 6
·
0⤊
1⤋
f(a) x f(b) = 16^(a) x 16^(b) = 16^(a + b) = f^(a + b)
2007-03-19 00:25:20
·
answer #3
·
answered by Como 7
·
0⤊
0⤋
f(a) x f(b)=(16^a) x (16^b)=16^(a+b)=f(a+b)
2007-03-18 23:00:45
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
f(u) = 16^u,so
f(a) = 16^a , and f(b) = 16^b
f(a) x f(b) = 16^a x 16^b
= 16^(a+b) = f(a+b)
2007-03-18 23:20:52
·
answer #5
·
answered by Kinu Sharma 2
·
0⤊
0⤋